2012
DOI: 10.1152/physiolgenomics.00085.2012
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome correlation analysis identifies two unique craniosynostosis subtypes associated with IRS1 activation

Abstract: . Transcriptome correlation analysis identifies two unique craniosynostosis subtypes associated with IRS1 activation. Physiol Genomics 44: 1154-1163. First published October 16, 2012 doi:10.1152/physiolgenomics.00085.2012The discovery of causal mechanisms associated with nonsyndromic craniosynostosis has proven to be a difficult task due to the complex nature of the disease. In this study, differential transcriptome correlation analysis was used to identify two molecularly distinct subtypes of nonsyndromic cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Similarly, MSX2 and IGF1 were upregulated in sagOB-Fs with low BrdU incorporation and both MSX2 and IGF1 have well established roles in osteoblast differentiation. [55-57] Previous studies in our laboratory identified an IGF1 subtype within our craniosynostosis population [58] suggesting an important role of IGF1 in the development of craniosynostosis. Our correlation analysis also identified genes that while not found in the GO search, contribute to osteoblast biology.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, MSX2 and IGF1 were upregulated in sagOB-Fs with low BrdU incorporation and both MSX2 and IGF1 have well established roles in osteoblast differentiation. [55-57] Previous studies in our laboratory identified an IGF1 subtype within our craniosynostosis population [58] suggesting an important role of IGF1 in the development of craniosynostosis. Our correlation analysis also identified genes that while not found in the GO search, contribute to osteoblast biology.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, gain-of-function mutations in IGF1R have been identified in some non-syndromic craniosynastosis where the mechanism seems to be through activation of IRS1. 56 IGF-1 is likely to regulate both local and systemic energy metabolism. For example, it has been shown that during osteoblast differentiation the cells that are in a predifferentiation stage have lower number of active mitochondria and are more glycolytic in their energy consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Various strategies have been employed to overcome these obstacles, ranging from protocol standardization across research centers to mandatory reporting standards such as MIAME (Beyer et al, 2007;Brazma et al, 2001). These strategies, coupled with public and private gene expression data repositories have greatly facilitated biomarker discovery efforts; however, a large number of these studies are required to generate the necessary statistical power and leverage to fuel these discoveries (Kodama et al, 2012;Stamper et al, 2012).…”
Section: Discussionmentioning
confidence: 99%